Using a Portfolio as an Example of an Alternative Assessment (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Assessment is collecting and evaluating information about an individual’s skills, knowledge, or performance to make decisions. It serves to find out about learning outcomes, identify strengths and weaknesses, and guide instruction. It is not unknown that assessment plays a crucial role in education, as it offers precious data about both individual and collective performance, leading to improvements. It also helps teachers customize instructions that meet the unique needs of their students. Furthermore, it aids in program evaluation and resource allocation. As assessment regards every stage of education, young learners should also be assessed, so that teaching them becomes more fruitful for everyone. As young learners demand special treatment, this article aims to discuss the ways of evaluating them properly.